Examining the Influence of Marketing and Human Resources Strategies on Financial Stability in Retail Businesses - Anak Agung Gede Wijaya; Marwan Effendi; Masruchan Masruchan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the joint influence of marketing strategy and human resource strategy on financial stability in retail businesses operating under increasingly volatile and technology driven market conditions. Retail firms face persistent challenges related to demand uncertainty, workforce dependency, and financial vulnerability, yet existing studies largely examine marketing and HR strategies as separate performance drivers. This research aims to address this gap by analyzing their direct and interactive effects on multidimensional financial stability. A quantitative explanatory design was employed using survey data from senior retail managers combined with audited financial reports. Structural equation modeling was applied to test causal relationships, while artificial intelligence based predictive modeling was used to enhance analytical robustness and capture non-linear patterns. The results show that both marketing strategy and human resource strategy have significant positive effects on financial stability. More importantly, their interaction effect is also statistically significant, indicating that strategic alignment between marketing and HR strengthens liquidity resilience, earnings consistency, and overall financial sustainability beyond their individual contributions. The AI model confirms these findings by identifying both strategies as the most influential predictors of financial stability, surpassing traditional firm characteristics. These findings demonstrate that financial stability in retail is not merely driven by accounting efficiency but fundamentally shaped by synchronized strategic capabilities. This study contributes to the literature by integrating marketing and HR strategies into a unified financial stability framework and extending retail finance research toward a multidimensional stability perspective. Managerially, the results emphasize the importance of coordinated investments in marketing capability and human capital development to achieve sustainable retail financial resilience.